Some Immunological Parameters Paraw in Women with vaginal candidiasis (Baghdad Science Journal, 2007)
This study was conducted to know some Immune responses in women with vaginal candidias is by Candidia species. Hemoglubin (Hb) was decreased significantly in patient women comparing with control group. The differential count of Blood cells revealed that neutrophils and monocytcs were increased significantly in patient women comparing with control group. The percentage of the Phagocytosis index was decreased significantly in patient women (66.45 + 15.05) comparing with control group (73.72 + 3.77) and the T- lymphocytes were decreased also in patient women (57.75 + 18.787) comparing with control group (74.25 + 7.759).